2021
DOI: 10.1002/bem.22352
|View full text |Cite
|
Sign up to set email alerts
|

Static Magnetic Field (0.2–0.4 T) Stimulates the Self‐Renewal Ability of Osteosarcoma Stem Cells Through Autophagic Degradation of Ferritin

Abstract: Static magnetic field (SMF) can alter cell fate decisions in many ways. However, the effects of SMF on cancer stem cells (CSCs) are little-known. In this particular study, we evaluate the biological effect of moderate-intensity SMF on osteosarcoma stem cells (OSCs) and try to clarify the underlying mechanisms of action. First, we demonstrated that prolonged exposure to SMF induced the proliferation and tumorsphere formation in K7M2 and MG63 OSCs. Moreover, SMF promoted the release of ferrous iron (Fe 2+ ) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Moreover, the modulation in kinetic parameters of CAT, CYP-450, SOD, and MDA concentration and iNOS enzymes in response to ELF EMF [267][268][269] and the negligible effects on GPX [270] indicates an interaction between the ELF EMF and the enzymological system. SMF promoted the release of ferrous iron (Fe 2+ ) and induced the production of ROS in osteosarcoma stem cells [271]. Superoxide increased in the micronucleus and mitochondria with an exposure-response relationship and cytosolic superoxide increased at 10 µT in SH-SY5Y and C6 cells [272].…”
Section: Ros (Such As Superoxide [Omentioning
confidence: 99%
“…Moreover, the modulation in kinetic parameters of CAT, CYP-450, SOD, and MDA concentration and iNOS enzymes in response to ELF EMF [267][268][269] and the negligible effects on GPX [270] indicates an interaction between the ELF EMF and the enzymological system. SMF promoted the release of ferrous iron (Fe 2+ ) and induced the production of ROS in osteosarcoma stem cells [271]. Superoxide increased in the micronucleus and mitochondria with an exposure-response relationship and cytosolic superoxide increased at 10 µT in SH-SY5Y and C6 cells [272].…”
Section: Ros (Such As Superoxide [Omentioning
confidence: 99%
“…Ferritinophagy is the process by which nuclear receptor coactivator 4 (NCOA4) releases the iron stored in ferritin to LIP and triggers ferroptosis 142 . A study conducted on osteosarcoma CSCs showed that exposure to a static magnetic field stimulates NCOA4-mediated ferritinophagy, promoting CSC proliferation and self-renewal 143 . Higher levels of glutathione peroxidase 4 (GPX4) and cystine/glutamate antiporter solute carrier family 7 member 11 (SLC7A11) protect esophageal CSCs from ferroptosis, which is induced by increased intracellular iron content.…”
Section: Biological Properties Of Cscsmentioning
confidence: 99%
“…Similarly, the induction of ferritin autophagy mediated by NCOA4 increases the sensitivity of aggressive glioblastoma cells to ferroptosis ( 49 ). However, in a specific study, researchers evaluated the effect of long-term moderate-intensity static magnetic field (SMF) on osteosarcoma stem cells and found that exposure to SMF-activated NCOA4, induced ferritin autophagy, increased intracellular Fe 2+ levels, and promoted the self-renewal ability of osteosarcoma stem cells ( 50 ). Concerning these inconsistent results, we hypothesize that NCOA4’s effect on CSCs could rely on the base Fe 2+ level in LIP, which is sustained within certain limits.…”
Section: Iron Metabolism In Cscsmentioning
confidence: 99%